Artificial Intelligence in STEM Education - William J. Triplett (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
The study examined Artificial Intelligence in STEM Education research crucial role in facilitating personalized learning, advanced analytics, and instructional automation. The primary goal of this research is to explore the effectiveness of AI in advancing STEM education. The specific objectives include assessing the practical challenges in integrating AI, examining the efficiency of various AI-enabled pedagogical strategies, and evaluating the short-term and long-term impacts of AI utilization in STEM subjects. The outcomes of this study are expected to provide valuable insights that could benefit educators, curriculum developers, policymakers, and researchers. Additionally, the findings may contribute to the development of innovative strategies for effectively integrating AI into STEM education, thereby potentially enhancing students, learning outcomes